Coloring technology for plastics - Harris, Ronald M. (Society of Plastics Engineers ; Plastics Design Library, 1999)
Focuses on developments in plastics coloring. The first section covers pigments and dyes with information on their chemistry, use, food contact approval, and durability. The second section focuses on effective pigment incorporation and discusses factors that influence it, as well as dispersing aids, dispersion methods, and ways to improve process ability and increase efficiency. In the section on the testing of colored products, methods to decrease variability, establish specifications, and select and design cost effective formulations are reviewed. New testing techniques such as FTIR and NIR are presented. In the next section the effect of colorants on properties of materials is analyzed with chapters covering their nucleating effect and polymer crystallization in their presence. Discussions of extrusion, injection molding, coating, and welding in relation to colorants are included throughout as are chapters on health and safety and special effects.